GAMBARAN KLINIS OTOMIKOSIS DI RS MARGONO SOEKARJO - Kinanthi, Rusy; Kusdaryanto, Wahyu Dwi; Darmawan, Anton Budhi; Krisniawati, Nia; Nur Hestiyanti, Rani Afifah (Mandala Of Health, 2024)
Otomycosis is a disease of the outer ear canal caused by fungal microorganisms. Signs found in patients with otomycosis may also vary, such as edema, redness of the outer ear canal, tragus pain, discharge, or fungal mass through the clinical examination. This study aimed to determine the clinical features of patients diagnosed with otomycosis at Margono Soekarjo Hospital. This research was a descriptive study with a cross-sectional approach using primary data from July-November 2022 at the ENT clinic, Margono Soekarjo Hospital. An ENT specialist took data through the stages of anamnesis and physical examination. After otomycosis is clinically diagnosed, further documentation is carried out on the patient’s examination sheet regarding the characteristics of the subject and the clinical features in the form of symptoms and signs experienced by the subject. The data analysis performed was a univariate analysis to demonstrate the frequency distribution of clinical features in the study subjects. The total samples obtained are 46 samples from 42 subjects diagnosed with otomycosis with an age range of 17-73 years, and the susceptible age to undergo otomycosis is 26-35 years. The most common symptom is itching (80,43%). Other commonly found symptoms are hearing loss (78,26%) and a sensation of blockage in the ears (73,91%). At the same time, the sign commonly found in the physical examination is a fungal mass (100%). The most typical form of fungal group is white mass. In addition, signs are frequently found in discharge (64,04%) and perforation (60,87%). Otomycosis is a common disease in young adults. Symptoms and signs of otomycosis vary, but the common symptoms are itching, hearing loss, and the sensation of blockage in the ears. At the same time, the common signs are fungal mass in the ear, discharge, and perforation of the ear.